TEACHERS' SURVEY ON THE TEACHING OF COMPUTING AS A COMPULSORY SUBJECT FOR PUPILS OF AGE 8 - Stankov, Emil; Jovanov, Mile; Jancheski, Metodija (IATED, 2023)
According to the European Union’s Council and the Commission on the implementation of the strategic framework for European cooperation in education and training, relevant and high-quality learning requires more innovative pedagogy and tools for developing digital competences, including e-literacy, computational and critical thinking, as well as coding and knowledge of algorithms. Furthermore, for this type of improvement, strong support for teachers, trainers and other educational staff is needed. In this paper we showcase the results of a survey analysis for the subject Computing for primary education, introduced in the academic year 2015/2016 in the Republic of Macedonia. The survey was conducted on a large sample of over 700 schoolteachers who had been teaching the subject for a year during the teacher training for the upcoming year. The survey covers 5 areas: the course format, computational thinking and coding topics, previous year’s training, questions on personal development and conditions for realization of the course. We present and analyze the results, and propose suggestions for improvements that may be valuable for every school system that tries to introduce this topic into the curriculum. Since the survey was conducted in many cities across our country, the results analysis is done by country regions, as well as by the teaching language.
Keywords: Computational thinking; teacher training; computing curriculum